Adolescents’ social strategies and behavioural/emotional problems - Sondaitė, Jolanta; Žukauskienė, Rita (Psichologija, 2004)
Current study is a first attempt to examine what patterns of social strategies could be identified among adolescents, and to explore how the use of particular strategies is associated with adolescent’s specific behavioural and emotional problems.The participants were 501 adolescents, 14-to –18 year-old (248 boys and 253 girls) from three secondary schools located in Vilnius, Lithuania and from two secondary schools located in sub-urban area.Social strategies were assessed using five subscales of the SAQ that measure cognitive strategies “in social context”. Behavioural/emotional problems were assessed using seven scales of YSR11/18: Withdrawn, Anxious/Depressed, Social problems, Attention problems, Aggressive behaviour, Delinquent behaviour.Patterns of strategy groups were examined by using a hierarchical clustering technique based on squared Euclidian distances (Ward, SPSS package). In this particular analysis we ended up using four-cluster solution. To investigate to what extent the adolescents’ in different social strategy groups would differ according to their anxiety-depression, withdrawal, attention problems, aggressive behaviour, delinquent behaviour, somatic complaints and social problems we carried out univariate two-way ANOVA for each variable separately with two between subject factors: Strategy group and Gender.It was shown first, that there were four homogenous groups of adolescents who seemed to deploy certain patterns of social strategies. All of them resembled the strategies described previously in the literature. The results show that 39% of adolescents deployed active optimistic strategy. They were typified by a moderately high level of success expectation, relatively high level of task-irrelevant behaviour, very low level of avoidance, very high level of mastery-orientation and very low level of pessimism. The results showed further that the adolescents who used active optimistic strategy showed lower levels of anxiety-depression, withdrawal and social problems. Nevertheless, they showed higher level of attention problems.Another group of the adolescents (14% from total sample) were identified as users of defensive functional strategy. They were characterized by the low level of success expectation, very high level of task-irrelevant behaviour, moderately low level of avoidance, high level of master -orientation, low level of pessimism. Defensive functional group also reported relatively low level of withdrawal, very high level of attention problems. However, girls’ levels of attention problems were much higher than the boys’ levels in the defensive functional group. They also showed relatively high level of social problems. Again, girls’ levels of social problems were much higher than the boys’ levels in the defensive functional group.Small group (12%) of the adolescents were identified as avoiders being typified by low level of success expectation, low level of task-irrelevant behaviour, very high level of avoidance, low level of master-orientation and high level of pessimism. They also showed high level of anxiety-depression, very high level of withdrawal, relatively low level of attention problems, very high level of social problems.Thirty-five per cent of the adolescents showed learned helplessness. They were characterized by moderately high level of success expectation, low level of task-irrelevant behaviour, high level of avoidance, very low level of master orientation and very high level of pessimism. The results further showed that the learned helplessness group showed relatively high level of anxiety-depression, high level of withdrawal, very low level of attention problems, relatively low level of social problems. The results showed that the membership of the strategy groups was associated in theoretically meaningful ways to the adolescents’ anxiety/depression, withdrawal, and social problems. Consequently, these results may help us to understand how different types of strategy patterns are related to emotional and behavioural problems.
Keywords: social strategies; behavioural problems; emotional problems; adolescents